Model for Digital Services in Libraries - Ahmad, Masitah; Abawajy, Jemal H.; Shahibi, Mohd Sazili; Dollah, Wan Ab Kadir Wan; Ismail, Saidatul Akmar; Saman, Wan Satirah Wan Mohd (Journal of Informatics and Mathematical Sciences, 2017)
With the new method of information delivery for the library, the quality of service and Digital Library issues become paramount importance. Various model and framework have been proposed to evaluate the Quality of Service in Digital Library. Unfortunately, features that contribute towards the Digital Library services quality have not been factored into the design of most existing quality of services model in Digital Library. This paper presented a result of hypothesis testing which eventually proposed a new conceptual model on the service quality of the digital library. This model incorporated two new features that determine the right third-party source services. It also offers an opportunity for further investigation for evaluating the service quality effectiveness in the digital library. It is conforming to the study backgrounds through a variety of research designs and settings by examination of the hypotheses presented in this study. Survey research designs employing third party sources services as a sample in the model would best match the requirements for validating the proposed framework. The result shows that all three hypotheses are supported. As a result, we propose a conceptual model for evaluating the service quality of the digital library and further analyze the effectiveness model with several contributing features grouped as a thirdparty source.